Resource utilization and ionization modification of waste starch from the recycling process of old corrugated cardboard paper. (1st October 2020) - Lin, Lingrui; Yang, Jie; Ni, Shuzhen; Wang, Xiu; Bian, Huiyang; Dai, Hongqi
Abstract: Generally, the mechanical strength and stiffness of old corrugated cardboard (OCC) waste paper are decreased after multiple recycling procedures. Surface sizing starch, which is extensively used in the surface sizing of paper making, accumulates after dissolving from the fibers and is transformed into pollutant during the OCC re-pulping process. To overcome the pollution and reutilization problem of the waste starch during the recycling process of OCC paper, waste starch was ionized using hydrogen peroxide (H2 O2 ) to improve the mechanical properties of OCC paper during the reutilization. The results showed that the carboxyl group of waste starch increased with an increasing degree of ionization, resulting in enhanced copper ion adsorption capacity. Furthermore, the retention rate of the modified starch in the wet-end increased from 18.0% to 48.2%. The OCC paper presented the highest burst index and tensile strength of 8.94 kPa m 2 /g and 112.5 N m/g, respectively, when MS-2 was added. This work has great significance for implementation of the cleaning production of OCC waste papers and the reutilization of the waste starch. Graphical abstract: Image 1 Highlights: Waste starch was ionized to improve the mechanical properties of OCC paper. The starch content in OCC pulp wastewater reached 4.5–4.8 g/L. The waste starch was oxidized by H2 O2 to give anion carboxylic groups. The retention rate of the modified starch was 30.2% higher than waste starch.